Pseudo-acetylation of K326 and K328 of actin disrupts Drosophila melanogaster indirect flight muscle structure and performance - Viswanathan, Meera C.; Blice-Baum, Anna C.; Schmidt, William; Foster, D. Brian; Cammarato, Anthony (Frontiers in Physiology, 2015)
In striated muscle tropomyosin (Tm) extends along the length of F-actin-containing thin filaments. Its location governs access of myosin binding sites on actin and, hence, force production. Intermolecular electrostatic associations are believed to mediate critical interactions between the proteins. For example, actin residues K326, K328 and R147 were predicted to establish contacts with E181 of Tm. Moreover, K328 also potentially forms direct interactions with E286 of myosin when the motor is strongly bound. Recently, LC-MS/MS analysis of the cardiac acetyl-lysine proteome revealed K326 and K328 of actin were acetylated, a post-translational modification (PTM) that masks the residues’ inherent positive charges. Here, we tested the hypothesis that by removing the vital actin charges at residues 326 and 328, the PTM would perturb Tm positioning and/or strong myosin binding as manifested by altered skeletal muscle function and structure in the Drosophila melanogaster model system. Transgenic flies were created that permit tissue-specific expression of K326Q, K328Q, or K326Q/K328Q acetyl-mimetic actin and of wild-type actin via the UAS-GAL4 bipartite expression system. Compared to wild-type actin, muscle-restricted expression of mutant actin had a dose-dependent effect on flight ability. Moreover, excessive K328Q and K326Q/K328Q actin overexpression induced indirect flight muscle degeneration, a phenotype consistent with hypercontraction observed in other Drosophila myofibrillar mutants. Based on F-actin-Tm and F-actin-Tm-myosin models and on our physiological data, we conclude that acetylating K326 and K328 of actin alters electrostatic associations with Tm and/or myosin and thereby augments contractile properties. Our findings highlight the utility of Drosophila as a model that permits efficient targeted design and assessment of molecular and tissue-specific responses to muscle protein modifications, in vivo.